Prebiotic products based on kepok banana starch (Musa paradisiaca Formatypica) and moringa (Moringa oleifera) as functional food for female wistar rats - Luthfiyah Fifi; Ikayanti Retno; Dwipajati (BIO Web of Conferences)
Background: Colon cancer ranks as the 5th most common cancer worldwide, with over one million new cases reported between 2015 and 2018. Resistant starch found in Kepok Banana extract may have potential in colon cancer prevention. Additionally, diets rich in iron and vitamin C contribute to chronic disease prevention. Moringa leaves, rich in vitamin C, enhance iron absorption. This study evaluated the growth of Lactobacillus and Shigella spp in female rats given Moringa-Banana starch (MBS) as a prebiotic supplement. Results showed significant differences in gut microbiota with MBS consumption, with higher concentrations of beneficial bacteria and reduced levels of pathogenic bacteria observed in the group receiving the highest MBS dose. These findings suggest that MBS could be a potential prebiotic candidate for further development.